Manajemen Kepala Madrasah Dalam Mencapai Visi, Misi, dan Sasaran Pada MIN 31 Kabupaten Aceh Utara - Syukri Syukri; Hasan Hasibuan; Zulfikar Ali Buto Siregar (Program Studi Manajemen Pendidikan Islam, 2023)
This study aims to determine planning, implementation, evaluation and supporting and inhibiting factors for the management of the Madrasah Principal in achieving the Vision, Mission and Targets at MIN 31 North Aceh District of North Aceh. Sources of data in this study included the Head of Madrasah, Deputy Head of Curriculum, and teachers of North Aceh MIN 31 North Aceh. This study uses a qualitative method with a descriptive approach. Data collection techniques in this study include observation, interviews and documentation. The results of the study show that first, planning for the management of the madrasah head in achieving the vision, mission and goals of North Aceh MIN 31 is carried out Formulation of character education programs that are integrated with the madrasah curriculum, holding activities to commemorate Islamic holidays, social services, holding congregational midday prayers, socialization of academic regulations, and monthly, mid-semester and annual coaching, and giving rewards and sanctions both routinely and incidentally. Second, the management of Madrasah heads in achieving the vision, mission and goals of MIN 31 North Aceh is carried out at MIN 31 North Aceh is carried out by determining the types of extracurricular activities that suit the talents and interests of students and determining character values ​​in each type of extracurricular activities by the coach extracurricular, Third, Evaluation of the management of the Madrasah head is carried out by determining the character values ​​to be instilled, the formation of the madrasa culture, and the supporting and inhibiting factors of the Madrasah Head in achieving the vision, mission and goals at MIN 31 North Aceh. The four supporting factors are: the principal's leadership factor, the educational qualification factor of all educational staff and education staff, the support factor from the community and school members including committee members and parents. While the inhibiting factors include the indiscipline of teaching and educational staff in carrying out programs, the lack of public understanding related to achieving the madrasah vision, mission and goals. and the lack of quality capabilities of all stakeholders in improving the quality of madrasas